Avenger - Forsyth, Frederick, 1938- (New York : Thomas Dunne Books, 2003., 2003)
Living a secret double life, lawyer Cal Dexter embarks on a deadly quest for vengeance that threatens global security, prompting CIA agent Kevin McBride to race against the clock to stop him.
Keywords: Government investigators -- Fiction; Revenge -- Fiction; New Jersey -- Fiction; Suspense fiction